The Effectiveness of Project Based Learning on Seventh Grade Students Reading Narative Text of SMPI Al Azhaar Tulungagung - Zuhdi, Ahmad Saifu Jamalludin (Yayasan Pendidikan Tanggui Baimbaian, 2024)
Framed in action research, the authors investigated the perceptions and experiences of a cohort of student-teachers as they learned about and explored for the first-time teacher research in a self-contained module as part of a four-year pre-service or initial English language teacher education (IELTE) programme in southern Argentina. This study aims to determine how effective the project-based learning program is in improving English reading skills of class VII SMPI Al Azhaar Tulungagung in the 2023/2024 academic year. This research uses experimental method. This research was conducted in the classroom, the population in this study were students who were in seventh grade junior high school in the 2023/2024 school year. The total sample in this study was 30 students. This study found that students' English reading skills improved after using the project-based learning method. The effectiveness can be seen from the difference between the pre-test result of 69,33 and post-test result of 74,33 which indicates the effectiveness of the learning outcome.